SISTEM MONITORING PENGONTROL SUHU DAN INTENSITAS CAHAYA PADA PENETAS TELUR PUYUH - Ibrahim Rizki; Kustanto Kustanto; Sri Siswanti (STMIK Sinar Nusantara, 2018)
Hatching egg is important in the creation of excellent seeds. The accuracy of care of room temperature conditions and microcontroller-based monitoring system is one of the first steps to meet the needs of quality quail seeds in the market. At the same time naturally, it is very difficult, because the parent quail is only able to incubate about 5 eggs. The use of automatic egg hatchery is one of the solutions. In this Scripsir research is made automatic quail egg machine based on microcontroller atmega328. The control is able to control the temperature and humidity needed in hatching eggs. From the control result using a microcontroller, lamp and fan can be adjusted according to the temperature of the room on the egg hatch is by automatic control of the lamp life and the fan. Test results showed that an increase in hatching eggs by 13%.Keywords: Hatching eggs, Monitoring system, Climate control, Microcontroller.